Pulmonary Microscopic Polyangiitis Presenting as Acute Respiratory Failure from Diffuse Alveolar Hemorrhage - Roberts, Katharine K.; Chamberlin, Michael M.; Holmes, Allen R.; Henderson, Jonathan L.; Hutton, Robert L.; Hannah, William N.; Morris, Michael J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Microscopic polyangiitis and granulomatosis with polyangiitis are rare anti-neutrophilic cytoplasmic antibody-associated systemic vasculitides that predominantly affect small to medium sized vessels of the lungs and kidneys. These syndromes are largely confined to older adults and often present sub-acutely following weeks to months of nonspecific prodromal symptoms. While both diseases often manifest within multiple organ systems concurrently, the disease spectrum of microscopic polyangiitis almost always includes the kidneys, while granulomatosis with polyangiitis is most commonly associated with pulmonary disease. We present two cases of rapid onset respiratory failure secondary to diffuse alveolar hemorrhage in young active duty military personnel. After serological testing and surgical lung biopsy, both patients were diagnosed with microscopic polyangiitis with isolated pulmonary involvement. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 372-377)